Self-Transformation towards Divine Consciousness according to the Text of Tattwa Sangkaning Dadi Janma - Prasanthy Devi Maheswari; Relin D.E.; I Made Surada (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
There is a phase where humans begin to want to learn knowledge about divinity. At first, humans will begin to ask who they are, why they were born, what their purpose in life is and where they will go after completing their life? Humans will begin to feel that a human being is not actually a material body, but rather has power as a source of life within. A human being who wants to know the true nature of the self should go through a transformation process. This research uses the Tattwa Sangkaning Dadi Janma text as a research object and is also supported by other related research. This type of research is qualitative using literature review techniques including reference books, articles in scientific journals and online data searches to collect data. After the data is collected, it is then analyzed through interpretation with hermeneutical theory, and then determines conclusions. Then the results of this research are presented systematically in the form of a narrative. The awakening of divine consciousness will lead a person to a transformation process to know the true self, which in this research is by realizing that everything comes from God, realizing the essence of being a human, then by carrying out yoga as a path of transformation from ordinary consciousness to higher consciousness and finding the true self.